The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.2147/idr.s257851
|View full text |Cite
|
Sign up to set email alerts
|

<p>Trend and Characteristics of <em>Acinetobacter baumannii</em> Infections in Patients Attending Universal College of Medical Sciences, Bhairahawa, Western Nepal: A Longitudinal Study of 2018</p>

Abstract: Background: Acinetobacter baumannii is one of the major organisms causing nosocomial infections and is intrinsically resistant to multiple classes of antibiotics. The main objective of this study was to investigate the trend and characteristics of A. baumannii infections including its resistance pattern among patients attending Universal College of Medical Sciences, Teaching Hospital (UCMSTH) in Western Nepal, between January and December 2018. Patients and Methods: A total of 4862 clinical samples received at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 41 publications
(45 reference statements)
13
32
0
1
Order By: Relevance
“…Of the total (253) bacterial growth, more than ninety percent were Gram-negative bacteria, E. coli was the most predominant isolates among them. Our findings are consistent with previous studies reported from Everest Hospital, Baneshwor, 14 Alka Hospital, Jawlakhel, 31 National Public Health Laboratory, Teku, 32 Universal College of Medical Sciences, Bhairahawa, 33 B.P Koirala Institute of Health Sciences, Dharan, 34 Nobel Medical College, Biratnagar, 35 New Delhi, India, 36 Al-Najaf City, Iraq, 37 Shashemene Referral Hospital, Ethiopia, 38 and Mexico City, Mexico. 39 Slightly higher rate of Gram-negative bacterial infections were observed among female patients and could be due to higher prevalence of urinary tract infections among females.…”
Section: Discussionsupporting
confidence: 92%
“…Of the total (253) bacterial growth, more than ninety percent were Gram-negative bacteria, E. coli was the most predominant isolates among them. Our findings are consistent with previous studies reported from Everest Hospital, Baneshwor, 14 Alka Hospital, Jawlakhel, 31 National Public Health Laboratory, Teku, 32 Universal College of Medical Sciences, Bhairahawa, 33 B.P Koirala Institute of Health Sciences, Dharan, 34 Nobel Medical College, Biratnagar, 35 New Delhi, India, 36 Al-Najaf City, Iraq, 37 Shashemene Referral Hospital, Ethiopia, 38 and Mexico City, Mexico. 39 Slightly higher rate of Gram-negative bacterial infections were observed among female patients and could be due to higher prevalence of urinary tract infections among females.…”
Section: Discussionsupporting
confidence: 92%
“…The increased and variable rate of colistin resistance may be due to quality, concentration and extensive use of colistin in the livestock farming [ 34 ]. In clinical samples, E. coli remains as the most frequently isolated organisms which is consistent with several previous studies from Nepal [ 35 38 ]. The higher load of E. coli in urine samples may be due to their main role in urinary tract infections [ 35 ].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, urine constituted the highest frequency (28.2%) among all of the clinical samples. Our samples echo previous studies conducted in the International Friendship Hospital, Kathmandu [3], Universal College of Medical Sciences Bhairahawa [10], Human Organ Transplant Center [33], and Nobel Medical College, Biratnagar [35]. This may be due to the high association of Gram-negative bacteria with UTI, which is the most common among patients attending a hospital in Nepal [16].…”
Section: Overall Findingssupporting
confidence: 86%
“…Infections mediated by Gram-negative bacteria (GNB) constitute the major burden in low- and middle-income countries (LMICs) due to acquisition of various resistant genotypes. In particular, E. coli , K. pneumoniae , E. cloacae , and non-fermentative bacteria, such as P. vulgaris , A. baumannii , and Salmonella species, represent the major members of GNB that are associated with frequent and more severe forms of clinical manifestations, including urinary tract infection, bacteremia, and pneumonia [ 10 , 32 ]. More specifically, E. coli and K. pneumoniae represent the most predominant pathogens isolated from such infections [ 15 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation